The contribution of Geochemistry in the assessment of environmental conditions in soils and aquatic systems and in the application of remediation methodologies - ΒΑΡΝΑΒΑΣ Σ. Π. (Bulletin of the Geological Society of Greece, 2002)
A main present day geochemical application is the assessment of the environmental conditions prevailing in a variety of natural and anthropogenic environments and the application of remediation methodologies. For this aim geochemical studies lead to the determination of the concentration levels and the source of pollutants. In addition through biogeochemical studies the behavior of pollutants in various environments is determined (i.e. rate of enrichment or dilution in space and time, dispersion processes etc.). On the basis of the results of geochemical studies remediation methodologies and methodologies leading to prevention of toxic elements in getting into the food chain are applied while criteria are put for the quality of soils, water etc. In addition decision makers are helped to make the necessary and right decisions in the management of toxic waste.